Surgical Aneurysm Repair of Aneurysmal Subarachnoid Hemorrhage in Sub-Saharan Africa: The State of Training and Management - Dokponou, Yao Christian Hugues; ALIHONOU, THIERRY; Adjiou, Dognon Kossi François de Paule; Obame, Fresnel Lutèce Ontsi; Kpègnon, Nicaise Agada; Bankole, Nourou Dine Adeniran (My University, 2023)
Background In a resource-limited setting such as sub-Saharan African countries, neurosurgeons need training and fellowship for surgical repair of aneurysmal subarachnoid hemorrhage (aSAH). Surgical repair of ruptured aneurysms costs less and requires less instrumentation compared with endovascular procedures. The purpose of this study is to evaluate the state of training and management of aSAH in sub-Saharan Africa training centers. Methods An e-survey was sent as a Google Form to neurosurgeons and neurosurgical trainees in neurosurgery training centers in sub-Saharan Africa; responses were accepted from September 9 to October 23, 2022. Statistical analysis was performed using Microsoft Excel and JAMOVI 3.2. Results All 44 centers from 17 countries responded. Most of the respondents were neurosurgery residents (n = 30; 68.18%). The level of training on clipping was basic after completing the residency program (n = 18; 40.91%). Twenty respondents (45.45%) identified that fellowships on aneurysmal clipping and endovascular treatment are offered abroad. Thirteen participants (29.55%) indicated that endovascular treatment is available at their institutions. The most common challenges with lack of training for neurosurgical aneurysm clipping were scarce scholarship and collaboration with training centers from high-income countries (n = 33; 75%). The availability of intensive care unit beds also contributed to the presence of neurosurgical training of aneurysm clipping (12.1 ± 3.67 vs. 9.29 ± 5.82; P = 0.05). Conclusions In sub-Saharan African countries, the lack of collaborations with high-income countries for training through fellowships of young neurosurgeons for aneurysm repair seems to be the most important challenge that should be overcome.
Keywords: Surgery; aneurysm; Subarachnoid hemorrhage; Training; Sub saharan Africa.